Chronic thrombocytopenia and skeletal dysplasia in a 14-year-old girl with cystic fibrosis. Issue 11 (2016) - Thomassen, Jan C.; , Ilse J. Broekaert; Körber, Friederike; Simon, Thorsten; Rietschel, Ernst; Koningsbruggen-Rietschel, Silke van
No abstract available